2005
DOI: 10.1002/pse.197
|View full text |Cite
|
Sign up to set email alerts
|

Performance of steel–concrete composite structures in fire

Abstract: This paper presents a review of recent studies of the behaviour of steel-concrete composite structures in fire, including an assessment of research investigations and their implications on fire-resistant design of composite structures. The paper focuses on the three main parts of composite structure: floor systems, columns and joints. The section on composite floor systems includes bending behaviour of conventional composite floor/beam system with composite slabs on top of a solid steel I-beam; tensile membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 72 publications
0
24
0
Order By: Relevance
“…Usmani and Cameron (2004) extended the method further by modeling the deflected shape of the slab with a cubic polynomial before calculating the membrane forces. Further refinement includes the pulling in of columns under high floor membrane action based on the work of Wang (1996Wang ( , 2005 and published by HERA in New Zealand (Clifton, 1998).…”
Section: Slab Membrane Action In Firementioning
confidence: 99%
See 1 more Smart Citation
“…Usmani and Cameron (2004) extended the method further by modeling the deflected shape of the slab with a cubic polynomial before calculating the membrane forces. Further refinement includes the pulling in of columns under high floor membrane action based on the work of Wang (1996Wang ( , 2005 and published by HERA in New Zealand (Clifton, 1998).…”
Section: Slab Membrane Action In Firementioning
confidence: 99%
“…For CFT columns, the steel tube may experience local buckling at the ends or along the length under fire exposure. If local buckling occurs at the ends, then the column should be considered pinned, but there is no clear guidance on when that happens, only indications that the location of the local buckling depends on the axial load, the thickness of the steel tube, and the bond between the steel tube and the concrete core (Wang, 2005).…”
Section: Critical Assessmentmentioning
confidence: 99%
“…Experimental and analytical investigations involving full-scale fire tests indicated that tensile membrane action within the concrete floor slabs plays an important role in enhancing the fire resistance of composite buildings. The load carrying capacity of slab due to tensile membrane action is significantly higher than the slab under pure bending [2]. Tensile membrane action can occur when the slabs undergoes large vertical displacements.…”
Section: Introductionmentioning
confidence: 98%
“…Response phenomena occur during heating of a CFS column that influence failure but cannot currently be predicted with confidence [15]. The appropriate effective length of CFS columns in fire has received considerable research attention [16], yet available guidance, based almost entirely on computational modelling, may be unconservative. The reasons for and likely location of the formation of local buckling and failure of a CFS column remain unclear [16].…”
Section: Introductionmentioning
confidence: 99%
“…The appropriate effective length of CFS columns in fire has received considerable research attention [16], yet available guidance, based almost entirely on computational modelling, may be unconservative. The reasons for and likely location of the formation of local buckling and failure of a CFS column remain unclear [16]. The analysis in this paper seeks to determine whether some of the above uncertainties play roles in the performance of available structural fire design approaches.…”
Section: Introductionmentioning
confidence: 99%